Pengaruh Kualitas Layanan dan Perilaku Karyawan Berbasis OCB Terhadap Kepuasan Konsumen di Hotel Santika Dyandra Medan - Indoh Julito, JMLS Puti; Nazmah, Nazma (Jurnal Ilmiah Muqoddimah: Jurnal Ilmu Sosial, Politik dan Hummaniora, 2024)
The purpose of the study was to determine the effect of service quality and OCB-based employee behaviour on customer satisfaction at Hotel Santika Dyandra Medan. The research was located at Santika Dyandra Hotel Medan which was conducted from June-August 2024. The sample used in this study was 105 people. The sample technique used in this study is probability sampling. The data analysis technique used in this research is quantitative data analysis. Partially, service quality variables and OCB-based employee behaviour individually show a positive influence on customer satisfaction. Simultaneously, the positive effect of the two variables is also seen when tested simultaneously. The Adjusted R Square value in the Determinant Coefficient test (R-2) of 0.733 means that 73.3% of customer satisfaction variables can be explained by service quality variables and OCB-based employee behaviour. While the remaining 26.7% can be explained by other variables outside this model.Kata kunci:Â  Kualitas Layanan, Perilaku Karyawan, Kepuasan Konsumen